Invitación a la Elección y Coronación de la Reina de la Facultad de Ciencias de la Salud y del Ser Humano. - Llivi Ruilova, Danny Vicente (2024)
Dr. Silvana López Paredes, Dean of the Faculty of Health and Human Sciences of the UEB, extends the cordial invitation to the Election and Coronation of the Queen of the Faculty; with the participation of Ms. Lizeth Katherine Gaibor Guevara, representing the Disaster Risk Engineering career; Miss Karol Vázquez from Nursing; and Ms. Doménica Alejandra Camacho Pinos, representing the Physical Therapy career.